2010
DOI: 10.1097/qai.0b013e3181be6be2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tenofovir on Renal Function in HIV-Infected, Antiretroviral-Naive Patients

Abstract: Tenofovir is associated with greater effect on decline in renal function and a higher risk of proximal tubular dysfunction in antiretroviral naïve patients initiating antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
92
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 41 publications
11
92
3
2
Order By: Relevance
“…They found an identical prevalence as in our study, and any tenofovir (TDF) use, as well as any indinavir (IDV) use, was associated with a higher risk of CKD (5). A recent study investigated the effect of tenofovir on renal function in 1647 ARV-naïve HIV-infected patients (25). Again, this study focused on tenofovir exposure and concluded that tenofovir was associated with greater effect on decline in renal function.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…They found an identical prevalence as in our study, and any tenofovir (TDF) use, as well as any indinavir (IDV) use, was associated with a higher risk of CKD (5). A recent study investigated the effect of tenofovir on renal function in 1647 ARV-naïve HIV-infected patients (25). Again, this study focused on tenofovir exposure and concluded that tenofovir was associated with greater effect on decline in renal function.…”
Section: Discussionsupporting
confidence: 76%
“…Our study shows statistical association between ARV drugs and CKD that needs to be documented further to identify nephrotoxic mechanisms. Tenofovir and indinavir have been shown to be related to nephrotoxicity in many studies (2,5,6,10,11,25). Some factors (hepatitis B or C and diabetes) traditionally reported as related to CKD in persons with or without HIV-1 infection were not found to be independently associated with the occurrence of CKD in our analysis (5,26,27).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…metabolic alterations, diabetes, hypertension and cardiovascular events) [12][13][14]. It has been hypothesized that antiretroviral medications may have a direct effect in increasing the risk of renal dysfunction, and a variety of cART-related effects, including proteinuria, renal tubular damage, interstitial nephritis and overall declines in glomerular filtration rates, have been noted [15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%